Baseline Susceptibility of Filarial Vector Culex quinquefasciatus (Diptera: Cu-licidae) to Five Insecticides with Different Modes of Action in Southeast of Iran - Yaser Salim-Abadi; Mohammad Asadpour; Iraj Sharifi; Alireza Sanei-Dehkordi; Mohammad Amin Gorouhi; Azim Paksa; Zohre Tayyebi; Abbas Aghaei-Afshar (Tehran University of Medical Sciences, 2017)
Background: Culex quinquefasciatus (Diptera: Culicidae) is an important vector for many human diseases. The aim of this study was to evaluate the susceptibility level of larval and adult stages of Cu. quinquefasciatus to different groups of WHO recommended insecticides for vector control. Methods: Larval stages of the Culex mosquitoes were collected from their natural habitats in Rafsanjan County at Kerman Province, southeast of Iran in 2016. Insecticide susceptibility status of adult female Cx. quinquefasciatus against DDT (4%), deltamethrin (0.05%), malathion 5%, and bendiocarb (0.1%) were determined using WHO standard insecticide susceptibility test. Additional test was carried out to determine the susceptibility status of larvae of Cx. quinquefasciatus to temephos. Bioassay data were analyzed by Probit program. Results: Cx. quinquefasciatus adults showed resistance to all four groups of the tested insecticides according to the WHO criteria for resistance evaluation. The lethal concentrations for 50% mortality (LC50) and 90% mortality (LC90) of temephos against Cx. quinquefasciatus larvae were 0.18mg/l and 0.78mg/l, respectively. This finding also confirms resistance to temephos based on the WHO recommended instructions for resistance evaluation. Conclusion: Resistance to all groups of the tested insecticides should be considered for future vector control investigations in the study area.